Do government subsidies lead to TFP losses? A perspective on the formation of zombie firms - Ruying Chen; Danyu Liu; Lanyu Wu; Donghua Yu (PLoS ONE, 2025)
This study examines how government subsidies affect aggregate total factor productivity (TFP) through the formation of zombie firms in China. Using panel data of A-share listed firms from 2007 to 2022 and industry–province–year aggregates, we analyze both firm-level dynamics and aggregate productivity outcomes. The results show that subsidies reduce the exit probability of low-productivity firms and significantly increase the likelihood of zombie firm formation. Although the prevalence of zombie firms fluctuates over time, it remains a persistent challenge. At the aggregate level, subsidies exert a negative impact on TFP, with zombie firm prevalence serving as a key mediating channel. The mediating effect is particularly strong in industries with a higher share of state-owned enterprises (SOEs), whereas regional differences stem from distinct mechanisms: subsidies more strongly induce zombie formation in Central–Western China, while the productivity drag of zombies is larger in the more competitive Eastern region. These findings highlight the unintended productivity costs of subsidy policies and underscore the need for more targeted and efficiency-oriented intervention.